Presence of an interferon signature in individuals who are anti-nuclear antibody positive lacking a systemic autoimmune rheumatic disease diagnosis - Wither, Joan; Johnson, Sindhu R.; Liu, Tony; Noamani, Babak; Bonilla, Dennisse; Lisnevskaia, Larissa; Silverman, Earl; Bookman, Arthur; Landolt-Marticorena, Carolina (Arthritis research & therapy, 2017)
Elevated levels of type I interferons (IFNs) are a characteristic feature of the systemic autoimmune rheumatic diseases (SARDs) and are thought to play an important pathogenic role. However, it is unknown whether these elevations are seen in anti-nuclear antibody-positive (ANA ) individuals who lack sufficient criteria for a SARD diagnosis. We examined IFN-induced gene expression in asymptomatic ANA individuals and patients with undifferentiated connective tissue disease (UCTD) to address this question. Healthy ANA control subjects and ANA titre (≥1:160 by immunofluorescence) participants meeting no criteria, meeting at least one criterion (UCTD) or meeting SARD classification criteria were recruited. Whole peripheral blood IFN-induced and BAFF gene expression were quantified using NanoString technology. The normalized levels of five IFN-induced genes were summed to produce an IFN5 score. The mean IFN5 scores were increased in all ANA participant subsets as compared with healthy control subjects. We found that 36.8% of asymptomatic ANA and 50% of UCTD participants had IFN5 scores >2 SD above the mean for healthy control subjects. In all ANA subsets, the IFN5 score correlated with the presence of anti-Ro/La antibodies. In the asymptomatic ANA subset, this score also correlated with the ANA titre, whereas in the other ANA subsets, it correlated with the number of different ANA specificities. Development of new SARD criteria was seen in individuals with normal and high IFN5 scores. An IFN signature is seen in a significant proportion of ANA individuals and appears to be associated with ANA titre and type of autoantibodies, rather than with the presence or development of clinical SARD symptoms.